Study of consumption of blood and blood components in emergency obstetrics patients - Vaghela, Zeel R.; Mewada, Bhavna N.; Patel, Akash J.; Kapadia, Labdhi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Most of the emergencies in the labour room, which require blood and blood product transfusion includes, complications of abortion, placenta previa, ruptured ectopic pregnancy and haemorrhage in labouring patients. Patients may come with severe anaemia and may develop post-partum haemorrhage or any other complications resulting in massive blood loss and rapid deterioration in well-being of the mother. Blood transfusion has become life-saving in management of haemorrhage in obstetric patients. However, like all treatments, it may result in acute or delayed complications. Methods: This retrospective study has included the patients who came with obstetric emergencies requiring blood and blood products during antepartum, intrapartum and postpartum period at the obstetrics and gynaecology department, at tertiary care hospital between December 2022 to December 2023. Results: Multigravida patients required more blood transfusion (69.23%) compared to primigravida (30.76%). Anaemia (38.46%) was the commonest indication for blood transfusion followed by post-partum haemorrhage (21.53%). Fever and shivering (3.07%) were seen to be the commonest adverse reactions. This study observed 92.3% live birth and 7.7% intrauterine foetal demise. Wound gap developed in 3(4.61%) patients following blood and blood products transfusion. Conclusions: Transfusing blood or its components holds utmost importance in comprehensive obstetric care, as emphasised by the current study. Haemorrhage in labouring patients and anaemia are leading causes of maternal morbidities and mortalities. The most effective outcomes in management are achieved through a carefully planned multidisciplinary protocol. Prompt availability of blood and blood components helps to avert mortality in a considerable number of cases.